The Role of L1 in Foreign Language Teaching Classrooms - Mustafa Durmuş (Sakarya University Journal of Education)
In the language teaching classes; there may be more than one language asthe language of verbal and written instructions, introduced by the instructoror through course materials, the questions directed to the instructor or theexplanations of the instructor about subjects which are not understood, orabout learner questions and statements. It is possible to divide theselanguages into three groups: target language, medium of instruction, and nativelanguage. In language teaching classrooms, determining the place, the order andthe ratio of these languages (target language, medium of instruction, andnative language) according to levels and language teaching contexts is one ofthe basic problematics in the development of pedagogical reasoning skills ofinstructors and management of teaching. This paper discusses, the place andfunction of the native language of the learners and what they should be,especially in the context of foreign language teaching among theseproblematics. In general, it is observed that instructional attitudes towardsthe use of native language are “complete prohibition”, “allowed as little aspossible”, “consciously legitimize the use of certain situations”. This paperfocuses on the role of native language of learner in foreign language teachingclassrooms, presented data and views by means of literature review and supportsthe idea, “Native language; if threatens the priority of target language can be‘the single biggest threat’ in foreign language class on the other hand, if itcan be used in ‘systematic, selective and reasonable doses’ it can be ‘the mostimportant ally a foreign language can have’.”